Toward Ethical Consumer Behavior: Islamic Perspective (A Theoretical Framework of Investigating the Determinants) - Firmansyah, Fani; Ika Prajawati, Maretha (International Journal of Engineering and Technology, 2019)
Today consumers take into consideration of the value from aproducts or services, in line with the development in information technology, even easier entering the world widespread. The growing market rapidly today, consumer needs are not limited to, the diverse product selection and even lead to the purchase of the attitude that is far from rational. The current challenges is about the motivation of consumer to consume the products and services and also the behaviour to consume. This article tries to explore how the characteristics of a consumer in buying behavior directed towards ethical consumption behavior. In the concept of Islam, a Muslim is given certain rules in doing so is not excessive consumption and think rationally. There are several factors that can influence the behavior of a Muslim in the activity of consumption because in fact, consumption of goods and services will lead to social change directly and indirectly and also environmental problems.Â